Fabrication of Tantalum and Hafnium Carbide Fibers via ForcespinningTM for Ultrahigh-Temperature Applications - Harold O. Lee; Patricia H. Caraballa; Avi G. Bregman; Nelson S. Bell; James R. Nicholas; Marissa Ringgold; LaRico J. Treadwell (Advances in Materials Science and Engineering)
In this work, a novel method for producing ultrafine tantalum and hafnium carbide fibers using the ForcespinningTM technique via a nonhalide-based sol-gel process was investigated. An optimal solution viscosity range was systematically determined via rheological studies of neat PAN/DMF as a function of fiber formation. Subsequently, ForcespinningTM parameters were also systemically studied to determine the optimal rotational velocity and spinneret-to-collecting rod distance required for ideal fiber formation. TaC and HfC fibers were synthesized via ForcespinningTM utilizing a mixture of PAN and refractory transition metal alkoxides (i.e., tantalum (V) ethoxide and hafnium (IV) tert-butoxide) in DMF solution based on optimal conditions determined from the neat PAN/DMF. In all instances after calcination, powder X-ray diffraction (PXRD) and energy dispersive spectroscopy (EDS) indicated that TaC and HfC fibers were produced. TGA/DSC confirmed the chemical stability of the resulting fibers.